Strategies to Promote Tourism in the Metropolitan Region of the Vale do Rio Cuiabá (RMVRC) for Local Development - Lopes, Yuri de Souza; Benini, Sandra Medina; Godoy, Jeane Aparecida Rombi de; Ravache, Rosana Lia (National Journal of City Management, 2024)
The objective of this study is to analyze the economic and sociocultural impact of tourism in the Metropolitan Region of the Cuiabá River Valley (RMVRC), highlighting how sustainable practices can enhance these benefits. The relevance of the topic is related to the growing importance of tourism as a catalyst for local development, especially in regions rich in cultural and natural heritage, such as Cuiabá. The methodology adopted includes a literature review and case analysis of the RMVRC, complemented by economic, social and environmental data, enabling a broad understanding of regional tourism dynamics. The results indicate that, despite the vast tourism potential, the region faces significant challenges in infrastructure and environmental management, especially with regard to sustainability. However, the research identified promising opportunities, such as the promotion of ecotourism and the development of cultural and gastronomic itineraries, which can strengthen tourist attractiveness. The conclusion highlights the need for an integrated approach, involving public-private partnerships, professional training, promotion of sustainable tourism and improvement of infrastructure, aiming to transform the RMVRC into a competitive and sustainable tourist destination.